Menuju Perbaikan Manajemen Penanggulangan Bencana di Indonesia - Christiana Yuni Kusmiati (Jurnal Administrasi Publik, 2005)
Considering that Indonesia has vulnerable natural and social environment, an effort and accurate disaster management approach is very important. We cannot neglect the fact that the current disaster management approach does not work properly. Correction to the current approach needs to be done as soon as possible. This articles aims to offer an analysis and recommendation to improve disaster management in Indonesia.Kata kunci: Comprehensive Vulnerability Management, kerangka kebijakan dan kerangka kelembagaan